"I'm Not Spanish, I'm from Spain": Spaniards' Bifurcated Ethnicity and the Boundaries of Whiteness and Hispanic Panethnic Identity. Issue 1 (January 2019) - Soto-Márquez, José G.
This study counters potentially premature demographic and sociological claims of a large-scale Hispanic transition into mainstream whiteness. Via in-depth interviews and ethnographic observations of recently arrived Spanish immigrants in the United States, it presents a distinctive shift in American categorization logic, whereby race and ethnicity switch in order of everyday importance. Despite Spanish immigrants' direct links to Europe and few structural social boundaries between them and mainstream U.S. whites, their everyday experience is of a largely "symbolic whiteness" that is subservient to the more consequential and essentialist Hispanic panethnic identity. Forced to maneuver this unique "bifurcated ethnicity, " Spaniards highlight a theoretically important deviation from the established ethnic options for European coethnics in the United States. Overall, Spaniards' ethnoracial adaptations and their identity vary by institutional sites, by social settings, and along gender lines. Their ethnic bifurcation brings into question the overall logic and stability of the U.S. Hispanic/white boundaries.